THE RESOLUTION OF THE CONFLICT BETWEEN FORESTRY WITH THE HOLDERS OF LAND RIGHTS IN THE AREA DESIGNATED AS FOREST AREA SEKAROH - Catur Bowo Subiarto (Fakultas Hukum Universitas Mataram, 2015)
This research aims to analyse the settlement of the conflict between forestry with the holders of land rights in the area designated as forest area Sekaroh. The legal issues that arise in this research include: How the legal process of determination of Sekaroh area of forest as forest area remains, How Legal certainty of land rights owned by communities in the Sekaroh forest area and how conflict resolution efforts between the Department of Forestry with the holders of land rights in the area designated as forest area Sekaroh. This research is the study of normative empirical, with the results of the study it was concluded that the legal process is the determination of the area of forest as forest area remains with the appointment mechanism, structuring and defining the boundaries of the layout as a forest area. The legal certainty of land rights owned by communities in the Sekaroh forest area were in accordance with the procedure of registration of land so that the Land East Lombok Regency Office publishes 7 certificate in 2001-2002 as evidence of property rights of communities against the right. Settling the conflict between forestry with the holders of land rights in the area of the forest area is designated as Sekaroh has done with communication, coordination and mediation, the inception of the regulations together with four Ministers about the procedures for settlement of land ownership in the forest area is a concrete step in solving the land/land in forest areas.Keywords: Forest Area, The Rights of Land, Conflict Resolution